Number concepts for the concept empiricist. (2nd April 2016) - Jones, Max
Abstract: Dove (2009) and Machery (2007) both argue that recent findings about the nature of numerical representation present problems for Concept Empiricism (CE). I shall argue that, whilst this evidence does challenge certain versions of CE, such as Prinz (2002), it needn't be seen as problematic to the general CE approach. Recent research can arguably be seen to support a CE account of number concepts. Neurological and behavioral evidence suggests that systems involved in the perception of numerical properties are also implicated in numerical cognition. Furthermore, the discovery of associations between spatial and numerical representations also lends independent support to a CE approach. Although these findings support CE in general, certain versions of the theory may need revising in order to accommodate them. In particular, it may be necessary to either jettison Prinz's (2002) Modal Specificity Hypothesis or to revise one's method for individuating modal representational formats.